Combustão iniciada por micro-ondas com radiação focalizada (FMIC) para decomposição de condimentos de origem vegetal para posterior determinação de metais por ICP OES - Knorr, Camila de Lellis (2011)
In this work the focused microwave induced combustion (FMIC) method was proposed for decomposition of spices, as Origanum vulgare L., Petrosolium sativum, Ocimum basilicum, Coriandrum sativum L. e Allium fistolosum for further Ba, Ca, Mn and Sr determination by inductively coupled plasma optical emission spectrometry (ICP OES). Origanum vulgare L. was chosen for optimization of parameters related to FMIC. For results comparison, microwave assisted wet digestion (MAWD), focused microwave assisted wet digestion (FMAWD), microwave induced combustion (MIC) and dry ashing were used to Origanum vulgare L. digestion. No statistical differences (ANOVA, confidence level 95%) were observed between the results obtained by MAWD, FMAWD, MIC, FMIC and dry ashing. Agreement for certified reference materials of apple leaves (NIST 1515) and peach leaves (NIS1547) after FMIC digestion ranged from 97 to 103%. Values of residual carbon content in digests obtained after MAWD, FMAWD, FMIC and MIC procedures were 0.93, 2.73, 0.17 e 0.04 mg de C/100 mg, respectively. The main advantages related to the use of FMIC are: the possibility to use diluted acids as absorbing solution, sample masses up to 1 g can be digested allowing lower limits of detection and digestion time is lower in comparison to the other methods evaluated in this work.